2016
DOI: 10.1111/jcmm.12808
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of extracellular S100A4 with RAGE prompts prometastatic activation of A375 melanoma cells

Abstract: S100A4, a member of the S100 protein family of EF‐hand calcium‐binding proteins, is overexpressed in various tumour entities, including melanoma, and plays an important role in tumour progression. Several studies in epithelial and mesenchymal tumours revealed a correlation between extracellular S100A4 and metastasis. However, exact mechanisms how S100A4 stimulates metastasis in melanoma are still unknown. From a pilot experiment on baseline synthesis and secretion of S100A4 in human melanoma cell lines, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 38 publications
(66 reference statements)
0
26
0
1
Order By: Relevance
“…Recently, Herwig et al demonstrated a role for high levels of extracellular S100A4, a member of the S100 calcium-binding protein family, in decreasing inter-endothelial tight junction integrity by using A375 human melanoma cells and an in vitro BBB model [ 54 , 55 ]. Paracrine-mediated signaling of S100A4 secreted from melanoma cells with its cognate receptor, receptor for advanced glycation end-products (RAGE), on endothelial cells enabled transmigration.…”
Section: Mechanisms Of Melanoma Brain Metastasismentioning
confidence: 99%
“…Recently, Herwig et al demonstrated a role for high levels of extracellular S100A4, a member of the S100 calcium-binding protein family, in decreasing inter-endothelial tight junction integrity by using A375 human melanoma cells and an in vitro BBB model [ 54 , 55 ]. Paracrine-mediated signaling of S100A4 secreted from melanoma cells with its cognate receptor, receptor for advanced glycation end-products (RAGE), on endothelial cells enabled transmigration.…”
Section: Mechanisms Of Melanoma Brain Metastasismentioning
confidence: 99%
“…S100A4, also called metastasis-associated protein, is universally overexpressed in a variety of tumor entities and is an independent marker for tumor progression, invasion, metastasis, poor survival, and prognosis (1). S100A4 influences cell motility, inflammation, angiogenesis, and apoptosis due to interaction between tumor cells and their microenvironment (59)(60)(61)(62)(63)(64). However, extracellular S100A4 seems to be of major importance in this context and, therefore, may possibly serve as a blood marker.…”
Section: S100 Proteinsmentioning
confidence: 99%
“…Because of the RAGE expression in melanocytes and melanoma cells, calprotectin seems to be an activator in these cells and it is a potential target for intervention in melanomagenesis (69). The latter should also be considered regarding interaction of S100A4 with RAGE (61,62). Another study presented evidence for S100A8/A9 as a novel predictive marker for ipilimumab treatment of metastatic Stage IV melanoma patients.…”
Section: S100 Proteinsmentioning
confidence: 99%
“…Az extracelluláris S100A4 (S100 kalciumkötő protein A4) molekula emelkedett szintje csökkenti a tight junction integritását humán melanomasejtekben [51]. A melanomasejtek S100A4 fehérjét választanak ki, amely parakrin módon kötődik receptorához.…”
Section: öSszefoglaló Közleményunclassified